2012
DOI: 10.5301/jbm.2012.9765
|View full text |Cite
|
Sign up to set email alerts
|

Survey of KRAS, BRAF and PIK3CA mutational status in 209 consecutive Italian colorectal cancer patients

Abstract: Molecular testing for KRAS and BRAF mutations in tumor tissue is a fundamental tool to identify patients with metastatic colorectal cancer (CRC) who are eligible for anti-EGFR monoclonal antibody therapy. We here report a molecular analysis by high-resolution melting analysis and direct sequencing of KRAS, BRAF and PIK3CA hot spot mutations in 209 Italian CRC patients. One hundred and ten patients (51%) were identified who were potentially nonresponders to anti-EGFR therapy: 90/209 patients (43%) harboring KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…A total 14 studies1314151617181920212223242526 with 1324 samples were included in our study and the average sample number was 94.5 (range 13 to 201). The earliest study was in March 200515, while the latest was in April 20132526.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total 14 studies1314151617181920212223242526 with 1324 samples were included in our study and the average sample number was 94.5 (range 13 to 201). The earliest study was in March 200515, while the latest was in April 20132526.…”
Section: Resultsmentioning
confidence: 99%
“…The dye included LCGreen(n = 1), Syto 9(n = 5), LightCycler LC480 High Resolution Melting Master(n = 6),EvaGreen(n = 1),and one study didn't mention about it17. The final volumes (μL) of HRM were 10 μL (n = 8), 20 μL (n = 4), 25 μL (n = 1), while one study didn't mention about it19. The quality of individual studies was relatively high, as all studies met 8 or more of the QUADAS criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 21 published articles containing data on BRAF and the clinicopathological characteristics were identified [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (Table 1). The search initially identified 2173 studies.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…[11], [13] It was demonstrated that KRAS or BRAF V600E mutations in CRC are associated with clinical resistance to treatment with epidermal growth factor receptor (EGFR)-targeted monoclonal antibodies. [14][16] However, the association between the BRAF V600E mutation and the clinicopathological characteristics of CRC remains controversial. [11] Nevertheless, it would be valuable to supplement standard clinical and pathological staging using molecular markers such as KRAS and BRAF V600E to more accurately classify subsets of patients for more effective clinical management.…”
Section: Introductionmentioning
confidence: 99%